2021
DOI: 10.3390/ijms22115932
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Three Type II Toxin-Antitoxin Systems in Model Bacterial Plant Pathogen Dickeya dadantii 3937

Abstract: Type II toxin-antitoxin (TA) systems are genetic elements usually encoding two proteins: a stable toxin and an antitoxin, which binds the toxin and neutralizes its toxic effect. The disturbance in the intracellular toxin and antitoxin ratio typically leads to inhibition of bacterial growth or bacterial cell death. Despite the fact that TA modules are widespread in bacteria and archaea, the biological role of these systems is ambiguous. Nevertheless, a number of studies suggests that the TA modules are engaged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…Proteins were identical in all, but one strains (NCTC 8457). In addition to D. dadantii [42], this TA family was also found (with at least 85% coverage and at least 50% identity) in several other marine bacteria: other Vibrios, Halomonas, Shewanella, Nitrincola, Rheinheimera, Marinomonas, Photobacterium, Edwardsiella. Acquisition through horizontal transfer among these marine species is thus likely at the origin of this large distribution.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Proteins were identical in all, but one strains (NCTC 8457). In addition to D. dadantii [42], this TA family was also found (with at least 85% coverage and at least 50% identity) in several other marine bacteria: other Vibrios, Halomonas, Shewanella, Nitrincola, Rheinheimera, Marinomonas, Photobacterium, Edwardsiella. Acquisition through horizontal transfer among these marine species is thus likely at the origin of this large distribution.…”
Section: Discussionmentioning
confidence: 81%
“…During our work, a new toxin also exhibiting a DUF4160 domain was recently identified in Dickeya dadantii, a plant pathogen bacteria, also found in fresh waters [42]. Protein comparison showed that VCA0497 has 64% identity with the newly identified DhiT toxin, while VCA0498 exhibits 59% homology with its associated DhiA antitoxin.…”
Section: Vca0497-vca0498 Encodes a Dhit/dhia Superfamily Type II Ta S...mentioning
confidence: 75%
See 1 more Smart Citation
“…oryzicola ( 35 ), Hok-Sok in Erwinia amylovora ( 36 ), EcnA-EcnB in Xanthomonas citri subsp. citri ( 37 ), CcdA-CcdB, Phd-Doc and DhiT-DhiA in Dickeya dadantii ( 38 ), and MazE-MazF in Agrobacterium tumefaciens ( 39 ).…”
Section: Introductionmentioning
confidence: 99%